Civil resistance and power politics : the experience of non-violent action from Gandhi to the present - Roberts, Adam, 1940-; Garton Ash, Timothy (OUP Oxford, 2011)
This widely-praised book identified peaceful struggle as a key phenomenon in international politics a year before the revolutions in Tunisia and Egypt confirmed its central argument. Civil resistance - non-violent action against such challenges as dictatorial rule, racial discrimination and foreign military occupation - is a significant but inadequately understood feature of world politics. Especially through the peaceful revolutions of 1989, and the developments in the Arab worldsince December 2010, it has helped to shape the world we live in. Civil Resistance and Power Politics covers most of.